New Insight in the Using of Core Needle Biopsy As First Line in Preoperative Diagnosis of Thyroid Nodule - Eaman Suud Khalifa; Ayser Hameed Latif (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: The diagnosis of thyroid nodule by core needle biopsy is different from post resection samplesbecause of difficulties in applying histological criteria for both samples due to limitation in core needlebiopsy sample .Objective: To assess the utility of core needle biopsy in diagnosis of thyroid nodule.Material and Method: We use core needle biopsy as first line method instead of fine needle aspirationand to reach final diagnosis after resection sample . Core needle biopsy results were divided to six groups)unsatisfactory, benign, indeterminate, follicular neoplasm, suspicious for malignancy and malignant)according to The Bethesda system for reporting thyroid cytopathology (1,2,3) .Result : A total of 45 thyroid nodules taken from 45 patients (30 female and 15 male) . Malignant changeswere seen in 19 nodules after surgery and 26 after core needle biopsy. Benign nodules were diagnosed in 11cases after surgery and in 12 cases after core needle biopsy . Final diagnoses were concluded for 34 nodules(76%). Twenty one nodules were diagnosed as malignant nodules and 13 nodules were diagnosed as benignnodules .Conclusions: Core needle biopsy is reliable and valuable tool for the diagnosis of thyroid nodule and canbeen used as an alternative to fine needle aspirate especially in patients with inconclusive results .